2017
DOI: 10.14295/oh.v23i3.1079
|View full text |Cite
|
Sign up to set email alerts
|

Non-structural carbohydrate metabolism and postharvest conservation of gerbera flowers

Abstract: The species Gerbera jamesonii Adlam has great economic importance in the ornamental sector, due to exuberance of floral stems. However, florists face some challenges such as postharvest handling and difficulty of conservation. Therefore, this study aimed to characterize the non-structural carbohydrate content in different floral stages of G. jamesonii var. Dawn and evaluate the effect of preservative solutions during the postharvest storage of this species. For this purpose, it was quantified TSS, RS and NRS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Studies on changes in carbohydrate compounds in cut flowers demonstrated strong regulation of sucrose and starch metabolism during floral development. Santos et al (2016) and Alves et al (2017) observed variations in the metabolism of nonstructural carbohydrates during floral opening and senescence of Lilium pumilum and Gerbera jamesonii, exhibiting great mobilization of compounds, which are used in the production of energy demanded by the floral development.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Studies on changes in carbohydrate compounds in cut flowers demonstrated strong regulation of sucrose and starch metabolism during floral development. Santos et al (2016) and Alves et al (2017) observed variations in the metabolism of nonstructural carbohydrates during floral opening and senescence of Lilium pumilum and Gerbera jamesonii, exhibiting great mobilization of compounds, which are used in the production of energy demanded by the floral development.…”
Section: Carbohydratesmentioning
confidence: 99%